2008
DOI: 10.2466/pr0.103.3.836-844
|View full text |Cite
|
Sign up to set email alerts
|

Marital Satisfaction before and after Deployments Associated with the Global War on Terror

Abstract: Previously, McLeland and Sutton (2005) assessed marital satisfaction among 46 male civilians and Reserve Component personnel, some of the latter having been alerted for a future deployment. Subsequently, marital satisfaction was also assessed for 74 male Active Component Army personnel who had recently returned from duty in a combat zone. Marital satisfaction scores were compared across personnel status. Mixed results were obtained from an analysis of variance comparing the five subgroups of personnel; however… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Factors such as length and frequency of deployments and SMs' psychological conditions such as PTSS, posttraumatic stress disorder ( PTSD), depression, anxiety, and dissociation have strained military relationships resulting in lower rates of marital satisfaction and intimacy (Allen, Rhoades, Stanley, & Markman, 2010;deBurgh, White, Fear, & Iversen, 2011;Knobloch & Theiss, 2012;Lara-Cinisomo et al, 2012;Mansfi eld et al, 2010;McLeland, Sutton, & Schumm, 2008;Melvin et al, 2012;Nelson-Goff et al, 2007;Sayers et al, 2009). Lara-Cinisomo and colleagues (2012) also found that the psychological health of the spouse was related to marital relationships in that spouses with poorer mental health experienced more relationship hassles.…”
Section: Research On Military Spousementioning
confidence: 94%
“…Factors such as length and frequency of deployments and SMs' psychological conditions such as PTSS, posttraumatic stress disorder ( PTSD), depression, anxiety, and dissociation have strained military relationships resulting in lower rates of marital satisfaction and intimacy (Allen, Rhoades, Stanley, & Markman, 2010;deBurgh, White, Fear, & Iversen, 2011;Knobloch & Theiss, 2012;Lara-Cinisomo et al, 2012;Mansfi eld et al, 2010;McLeland, Sutton, & Schumm, 2008;Melvin et al, 2012;Nelson-Goff et al, 2007;Sayers et al, 2009). Lara-Cinisomo and colleagues (2012) also found that the psychological health of the spouse was related to marital relationships in that spouses with poorer mental health experienced more relationship hassles.…”
Section: Research On Military Spousementioning
confidence: 94%
“…A review of 14 studies found that longer deployments, deployment extensions, and PTSD in military personnel were associated with psychological problems for the spouse [ 18 ]. Finally, there is evidence that the stresses of deployment may adversely affect marital satisfaction in military couples well after a return [ 19 ]. Thus, for a primary relationship to serve the much-needed support function for veterans, the impact of deployment on the veteran , the partner , and the relationship all need to be recognized and addressed.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, among a US peacekeeping unit of reserve personnel deployed for nine months or more, Schumm, Bell and Gade (2000) found that while some participants reported being less happy with their relationship during deployment, those who remained in their relationship post deployment showed no overall change in relationship satisfaction, suggesting that reductions in satisfaction during deployment may be transitory; moreover, among those who reported relationship problems, these were often present prior to deployment (Schumm, et al, 2000). Lastly, other research suggests that, compared to deployed participants, those anticipating a return or who have already returned from a deployment report lower marital satisfaction scores (McLeland, Sutton, and Schumm, (McLeland, Sutton, & Schumm, 2008). These findings provide contradictory evidence for the impact of deployment on relationships.…”
Section: Interpretative Phenomenological Analysis Of Soldier's Experiences Of Being Married and Serving In The British Armymentioning
confidence: 98%